2008
DOI: 10.1210/en.2007-0877
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Triggers Cardiac Fibrosis in the Heart of Diabetic Rats

Abstract: Diabetic cardiomyopathy is characterized by myocyte loss and myocardial fibrosis, leading to decreased elasticity and impaired contractile function. The study examines the downstream signaling whereby oxidative stress, induced by hyperglycemia, leads to myocardial fibrosis and impaired contractile function in the left ventricle of diabetic rats. It also examines the effects of dehydroepiandrosterone (DHEA), which prevents the oxidative damage induced by hyperglycemia in experimental models. DHEA was administer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
109
0
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 154 publications
(128 citation statements)
references
References 49 publications
15
109
0
4
Order By: Relevance
“…These findings are in agreement with other studies [26][27][28] . Consistent with their impaired cardiac function, diabetic rats developed myocardial fibrosis, the marked fibrotic regions (as observed by immunohistochemical staining), as well as deposition of collagen fibers in the interstitial spaces among cardiomyocytes (as observed by TEM), our observations are similar to those described in other reports [29,30] . Increased myocardial fibrosis is a major factor responsible for myocardial stiffness and eventual systolic [31,32] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in agreement with other studies [26][27][28] . Consistent with their impaired cardiac function, diabetic rats developed myocardial fibrosis, the marked fibrotic regions (as observed by immunohistochemical staining), as well as deposition of collagen fibers in the interstitial spaces among cardiomyocytes (as observed by TEM), our observations are similar to those described in other reports [29,30] . Increased myocardial fibrosis is a major factor responsible for myocardial stiffness and eventual systolic [31,32] .…”
Section: Discussionsupporting
confidence: 92%
“…First, to better understand the mechanism of action involved, cell culture study is needed to verify the causeeffect relationship with regards to the role of these signaling molecules in diabetic cardiac fibrosis. Second, it is known that diabetic cardiomyopathy is associated with significant increased oxidative stress which could lead to JNK activation and increased TGFβ [29,44] , so the contents of oxidative stress in the heart should be described. Third, there are only small number of rats in the study, this maybe limits statistical power and their results.…”
Section: Discussionmentioning
confidence: 99%
“…In the heart, TGF-β induces the differentiation of cardiac fibroblasts to the more active myofibroblasts, which can produce up to two-fold more collagen than their fibroblast precursors [34]. The increased expression of TGF-β in our diabetic patients is consistent with animal studies that showed upregulation of TGF-β mRNA in the hearts of diabetic animals [7,35].…”
Section: Discussionsupporting
confidence: 88%
“…Hyperglycemia and oxidative stress activate NF-κB, which regulates the expression of large numbers of genes including pro-inflammatory cytokines (TNF-α and IL-1β) and several genes correlated to fibrosis, including TGF-β, in the diabetic heart [7,36]. ALA can scavenge intracellular free radicals and therefore down-regulate proinflammatory redox-sensitive signal transduction processes including NF-κB activation [28,29].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation